Break Event Point Calculation Analysis and Margin of Safety as a Planning of Income Instrument: Analisis Pehitungan Break Even Point dan Margin of Safety Sebagai Alat Perencanaan Laba - Muhammad Fadhil Amiros; Yusleli Herawati; Ummasyroh (Politeknik Negeri Sriwijaya, 2022)
The development of coffee entrepreneurs in Indonesia is growing rapidly with the support of Indonesia as the fourth largest coffee producer in the world. The company's goal is to make a profit. This study aims to determine and explore the relationship between costs, profits and sales volume. This study uses the calculation of break even point and margin of safety as the basis for profit planning. The research method used is descriptive quantitative. Research data obtained through interviews and financial statements of the Colony Coffee Roastery. Furthermore, classifying costs into fixed costs and variable costs to calculate Break even point and Margin of safety and make profit planning. Based on the calculation of the Arabica coffee BEP of 40.2 kg and Rp. 15,109,992. Robusta coffee as much as 173.8 kg and Rp. 20,683,713 and house blend coffee as much as 140 kg and Rp. 22,264.15. The results of the calculation of the Margin of safety per month show that the three types of products experienced negative results. Koloni Coffee Roastery is advised to move quickly in increasing its sales, Colonies can make marketing strategies such as making promos, selling in smaller packages such as 200 grams and 500 grams and can also use Instagram ads or sell on e-commerce in order to attract customers on the three types of coffee products in order to increase profits in accordance with the results of the calculation of profit planning obtained. The three aspects of management are good and can be maintained.